2012
DOI: 10.1016/j.jalz.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A new informant‐based questionnaire for instrumental activities of daily living in dementia

Abstract: The Amsterdam IADL Questionnaire (Amsterdam IADL questionnaire is a registered trademark of Alzheimer Center VU University Medical Center, Amsterdam, The Netherlands) is a 70-item informant-based computerized questionnaire aimed at detecting early dementia and early-onset dementia. Initial results show that this questionnaire is a promising new tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 40 publications
2
118
0
2
Order By: Relevance
“…This assessment method optimizes the individual differences in complex daily activities. The median time to complete the questionnaire was 23 min (interquartile range 17-29) [6]. The online supplementary figure shows an example item of the questionnaire (for all online supplementary material, see www.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This assessment method optimizes the individual differences in complex daily activities. The median time to complete the questionnaire was 23 min (interquartile range 17-29) [6]. The online supplementary figure shows an example item of the questionnaire (for all online supplementary material, see www.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this need for a reliable and valid IADL questionnaire, a new questionnaire was recently developed [6]. In a previous study, we showed that the Amsterdam IADL Questionnaire© (a registered copyright of the Alzheimer Center of the VU University Medical Center) had good content validity, consisted of a single factor, had a high internal consistency and good test-retest reliability [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we do not think that this issue might have affected our results. We do suggest that future studies explore the possibility to use more elaborate ADL and IADL function tests [29,30] to further elucidate the role of impaired eye-hand coordination in developing functional disability. Finally, in this study we used a combination of an eye tracking system, a motion detection system, and a touch screen to quantify characteristics of eye-hand coordinated movements.…”
Section: Discussionmentioning
confidence: 99%
“…Since the Karnofsky Performance Status scale neither reflects neurological impairment such as hemiparesis nor cognitive deficit, its use for brain tumor patients to determine performance status is limited. Possibly specific activity of daily living scales, such as an instrumental activity of daily living scale developed for dementia, should be developed for brain tumor patients [14].…”
mentioning
confidence: 99%